The developing person : a life-span approach - Bee, Helen L.; Mitchell, Sandra (San Francisco : Harper & Row, 1980)
This is not a reorganized iteration of another Berger textbook, but rather a fully reconceived first edition exploring human development topic by topic. But as always with Berger, it is exceptionally accessible and compelling, distinguished by an engaging narrative voice, wide-ranging cultural perspective, and an emphasis on relating universal themes  to students' own lives.
Includes bibliographical references and index.
Keywords: Developmental psychology